The Hidden Violence of the Gynecology Clinic - Jesús Martín Galaviz de Anda; Octavio Maza Díaz Cortés; Carlos Alberto Prado Aguilar (Social Medicine Publication Group, 2016)
This study arose from the need to develop a critical understanding of clinical gynecology and involved the use of sociological techniques to analyze medical discourse. One of our key findings was the central role played by violence in the clinic. We carefully examined the socio-cultural devices employed in the patient/doctor relationship during interactions between both male and female physicians with women receiving reproductive care. An extensive literature already exists on the relations between doctors and patients, on gender violence, and on the domination and subordination of women. The current study offers an anthropological-descriptive examination of the relations within a biomedically-oriented clinic in Social Security system of Aguascalientes, Mexico. By analyzing the relationships formed between members of the healthcare team and the women patients they care for, this paper offers a critical look at how medical care is conceptualized within the priority area of Reproductive Health. Our findings offer doctors and other health professionals the opportunity to reflect on their behavior during interviews with patients. They also contribute to a richer, theoretical understanding of the role of gender violence within healthcare institutions that provide reproductive health services.